ANALISIS DAMPAK PEMBANGUNAN TOL CISUMDAWU SEKSI 2 FASE 2 TERHADAP PEREKONOMIAN PENDUDUK SEKITAR (Studi Deskriptif Kualitatif Terhadap Penduduk Dusun.Gawiru, Desa Girimukti, Kecamatan.Sumedang.Utara, Kabupaten.Sumedang-Provinsi Jawa.Barat) - TEGUH SANTOSA; TRISNAWATI KUSUMAWARDHANI (Develop: Jurnal Ekonomi Pembangunan, 2020)
The construction of the Phase 2 Cisumdawu toll road, located in Gawiru Hamlet, Girimukti Village, Sumedang District, Sumedang Regency, West Java, has an impact on the surrounding population. Both positive and negative impacts. The positive impact is that the surrounding population is empowered to do work outside of project work such as cooking services, clothes washing services, mess cleaning services and project offices, daily warehouse clerk services (checking supplies of material goods), field survey implementers, security, foreman, local subcontractor, plagman. The negative impact is the lack of buyers for traders around Jalan Cadas Pangeran. Infrastructure development should be followed by human development. According to UNDP, indicators of the success of human development include 1) equity, namely equitable distribution of development results, equitable distribution to be able to easily access primary human needs (clothing, food, shelter), the need for health services that have now gone through BPJS, the need for education which is now running with the SPP-free program for state schools, 2) the ability of every human being to be productive according to their creativity and innovation, 3) empowerment, namely growth and human resource development that the government strives for. This study uses a qualitative methodology by conducting in-depth interviews, while the paradigm of this research is constructivism